2021
DOI: 10.4103/ccd.ccd_731_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Time-kill Assay to Evaluate the Antimicrobial Efficacy of Garlic (Allium sativum) and Guava (Psidium guajava) Extracts on Periodontal Pathogens

Abstract: Background: The role of Gram-negative anaerobic periodontal pathogens in periodontal diseases has led to the loss of tooth-supporting structures. These diseases can be prevented by the inhibition of bacterial biofilm on the tooth surfaces. Many treatment modalities have been tried to prevent periodontal diseases. With the rise in resistance to synthetic antimicrobials, there is a requirement to develop natural antimicrobials for the control of periodontitis. Aim: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
1
0
1
Order By: Relevance
“…1) at 4 h for MIC or 2× MIC was not greater than a 3 log 10 -fold decrease in c.f.u. [25], which shows that not all bacterial cells are killed at 4 h and the bacteriostatic effect is not maintained at 24 h. A similar pattern has also been observed in another study with other natural compounds from garlic and guava [26]. It is also suggested that the antibacterial activity exhibited by C. ternatea anthocyanin fraction may be contributed by the synergistic activity of the anthocyanins in the fraction.…”
Section: Antibacterial Activity Of the C Ternatea Anthocyanin Fractio...supporting
confidence: 79%
“…1) at 4 h for MIC or 2× MIC was not greater than a 3 log 10 -fold decrease in c.f.u. [25], which shows that not all bacterial cells are killed at 4 h and the bacteriostatic effect is not maintained at 24 h. A similar pattern has also been observed in another study with other natural compounds from garlic and guava [26]. It is also suggested that the antibacterial activity exhibited by C. ternatea anthocyanin fraction may be contributed by the synergistic activity of the anthocyanins in the fraction.…”
Section: Antibacterial Activity Of the C Ternatea Anthocyanin Fractio...supporting
confidence: 79%
“…The chemical composition of P. guajava includes tannins such as guavins A-D and flavonoids [ 7 , 8 ], and its extracts have already been widely reported to have antimicrobial potential. Many studies have described the antimicrobial activity of different extracts from the leaves of P. guajava , such as methanolic [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], ethanolic [ 9 , 16 , 17 , 18 , 19 , 20 ], and aqueous [ 9 , 11 , 12 , 13 , 16 , 19 , 20 , 21 , 22 , 23 ], including the activity of methanolic extracts against methicillin-resistant Staphylococcus aureus (MRSA) strains [ 18 ]. The antimicrobial activity of the root [ 12 ] and fruit extracts [ 24 ] of P. guajava has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…E a sua patogênese também envolve fatores imunogenéticos e o estilo de vida (Akkaoui et al, 2020;Shetty et al, 2020) 2019). Dessa forma, torna-se necessária a investigação de novos agentes quimioterápicos e os fitoquímicos naturais isolados através dos extratos das plantas têm se destacado (Pasupuleti et al, 2023;Shetty et al, 2020;Shetty et al, 2021).…”
Section: Introductionunclassified